Synthesis and binding studies of two new macrocyclic receptors for the stereoselective recognition of dipeptides - Castilla, Ana Maria; Morgan Conn, M.; Ballester, Pablo (Beilstein Journal of Organic Chemistry, 2010)
We present here the design, synthesis, and analysis of a series of receptors for peptide ligands inspired by the hydrogen-bonding pattern of protein β-sheets. The receptors themselves can be regarded as strands 1 and 3 of a three-stranded β-sheet, with cross-linking between the chains through the 4-position of adjacent phenylalanine residues. We also report on the conformational equilibria of these receptors in solution as well as on their tendency to dimerize. 1H NMR titration experiments are used to quantify the dimerization constants, as well as the association constant values of the 1:1 complexes formed between the receptors and a series of diamides and dipeptides. The receptors show moderate levels of selectivity in the molecular recognition of the hydrogen-bonding pattern present in the diamide series, selecting the α-amino acid-related hydrogen-bonding functionality. Only one of the two cyclic receptors shows modest signs of enantioselectivity and moderate diastereoselectivity in the recognition of the enantiomers and diastereoisomers of the Ala-Ala dipeptide (ΔΔG01 (DD-DL) = −1.08 kcal/mol and ΔΔG01 (DD-LD) = −0.89 kcal/mol). Surprisingly, the linear synthetic precursors show higher levels of stereoselectivity than their cyclic counterparts.
Keywords: dipeptides; host–guest; macrocyclic; molecular recognition; receptors; stereoselective